Anticonvulsant Activity of Hydro Alcoholic Extract and Solvent Fractions of Biophytum umbraculum Welw. Syn (Oxalidaceae) Root in Mice - Fisseha N; Hammeso WW; Nureye D (Dove Medical Press, 2022)
Nebeyi Fisseha, Workineh Woldeselassie Hammeso, Dejen Nureye Department of Pharmacy, School of Pharmacy, College of Health Sciences, Mizan-Tepi University, Mizan-Aman, South West, EthiopiaCorrespondence: Nebeyi Fisseha, Tel +251913214835, Email nebeyifisseha@gmail.comBackground: Scientists and researchers continue to focus on medicinal plants as a potential source of lead chemicals in the search for and development of new antiepileptic medicines. Biophytum umbraculum Welw. Syn is used to treat epilepsy in Ethiopian traditional medicine. The anticonvulsant effect of Biophytum umbraculum Welw. Syn hydroalcoholic extract and solvent fractions was evaluated in this study since the claim has not been thoroughly explored.Methods: The plant's root was extracted using the maceration procedure, with aqueous, butanol, and chloroform as solvents. The maximum electroshock and pentylenetetrazol model tests were used to assess anticonvulsant activity. Mice were divided into five groups (n = 6) at random. The test groups received 100, 200, and 400 mg/kg of hydroalcoholic extract and solvent fraction, respectively. For the maximum electric shock test, the positive control groups received 25 mg/kg phenytoin and 200 mg/kg valproate for the pentylenetetrazol test. The negative control was given 10 mL/kg of pure water or 2% Tween 80.Results: There were no signs of toxicity in the hydroalcoholic extract or solvent extraction. When compared to the negative control, the hydro-alcoholic extract had a significant anticonvulsant effect in both the maximum electric shock test and the pentylenetetrazol test. In both cases, the butanol component had a comparable impact. In the pentylenetetrazol test, the chloroform fraction had a significant anticonvulsant effect when compared to the control at dosages of MB200 and MB400. Flavonoids, phenols, tannins, steroids, terpenoids, and saponins were found in both the hydroalcoholic and solvent fractions of the plant extract.Conclusion: The plant appears to have promising anticonvulsant properties, and it might be used to generate novel anti-epileptic drugs, according to this study.Keywords: epilepsy, seizure, pentylenetetrazol, anticonvulsant, Biophytum umbraculum